Implantação de um plano de manutenção em uma indústria de temperos: um estudo de caso - Dantas, Saulo de Morais (Universidade Federal Rural do Semi-Árido, 2018)
The management of the maintenance aims at a good planning in the maintenance of the machines, in order to avoid and prevent defects, and especially the failures. Failures occur, consequently we will have machine stops, which generates lower productivity, decrease in quality and rework. In this way, a proper maintenance planning of machines becomes extremely essential in a highly globalized and fierce scenario, where changes occur at all times, whose main objective is to deliver the products or services in the indicated time, with the requested quality and the projected quantity, always seeking the least possible loss, and with low maintenance cost. Thus, the present study discusses the planning of the implementation of a maintenance plan in a seasoning industry, located in the city of Mossoró / RN. Where a case study was carried out, thus elaborating a maintenance plan, based on the PDCA method of continuous improvement. Thus, the proper management of the maintenance department is able to guarantee several benefits to the organization, among them it is possible to list: Improved security, as the behavior of the facilities behave in a predictable manner, offering a lower risk for operations. And in addition, ensuring an increase in productivity of the company.
Monografia
Keywords: Planejamento; Gestão; Manutenção; Planning; Management; Maintenance; ENGENHARIAS::ENGENHARIA DE PRODUCAO